Dynamic Performance Analysis and Fault Ride-Through Enhancement by a Modified Fault Current Protection Scheme of a Grid-Connected Doubly Fed Induction Generator - Talani, Rameez Akbar; Kaloi, Ghulam Sarwar; Ali, Aamir; Bijarani, Muhammad Ali; Abbas, Ghulam; Hatatah, Mohammed; Mercorelli, Paolo; Touti, Ezzeddine (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
With the increase in reliance on doubly fed induction generator-based wind energy conversion systems (DFIG-WECSs), extracting maximum power from wind energy and enhancing fault ride-through (FRT) techniques meeting the grid code requirements is the foremost concern. This paper proposes a modified control scheme that operates in normal running conditions and during faults as a dual mode. The proposed control scheme operates in a coordinated wind speed estimation-based maximum power point tracking (WSE-MPPT) mode during normal running conditions to extract maximum power from wind energy and enhances the crowbar rotor active impedance-based FRT mode during faults. The proposed technique controls the rotor side converter (RSC) parameters during faults by limiting the transient surge in the rotor and stator currents. In this study, the transient behavior of the proposed technique is analyzed under a three-phase symmetrical fault with a severe voltage dip, and it is observed that, when the fault is over and the RSC is activated and connected to the system, a large inrush current is produced with transient oscillations; the proposed scheme suppresses this post-fault inrush current and limits the transient oscillation. During the FRT operating mode under a symmetrical fault, the simulation results of the proposed technique are validated by the conventional crowbar strategy. In contrast, during the WSE-MPPT operating mode under normal running conditions, a smooth achievement of system parameters after starting the inrush period to a steady state at fixed wind speed is observed.
Keywords: Doubly Fed Induction Generator; Fault Ride-through; Crowbar; Maximum Power Point Tracking; Rotor Side Controller (RSC)